Franklin's Christmas gift - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic, 1998)
When Franklin tries to decide which present he should give to the toy drive at school, he thinks that all his toys are too special to give away, but he soon realizes that none of them are special enough.
4.6
K-3
K-3.
380
Keywords: Christmas -- Fiction; Turtles -- Fiction; Generosity -- Fiction; Animals -- Fiction; Christmas -- Fiction; Turtles -- Fiction; Generosity -- Fiction; Animals -- Fiction